4.1k views
4 votes
If f(x) = 5x − 3, which expression represents its inverse function?

User P C
by
5.6k points

2 Answers

5 votes

Answer:

i dont thins that the answer ...

Explanation:

User Phuongnd
by
4.7k points
4 votes

Answer:


f ^(-1)(x)=(x+3)/(5)

Explanation:

To find the inverse of a function f (x) follow the steps below:

1) Make y = f (x)


y= 5x - 3

2) Solve for the variable x


y+3= 5x - 3+3


y+3= 5x


x=(y+3)/(5)

3) Exchange the variable x with the variable y


y=(x+3)/(5)

4) Make
y = f ^(-1)(x)


f ^(-1)(x)=(x+3)/(5)

Finally, the inverse of the function f (x) is:
f ^(-1)(x)=(x+3)/(5)

User Chris Forrence
by
5.1k points